Gensko zdravljenje sladkorne bolezni tipa 1 - Marušič, Tjaša (Placebo, 2022)
Type 1 diabetes is a chronic autoimmune disease caused by immune-mediated destruction of pancreatic ß cells that results in life threatening hyperglycaemia. Several genetic and environmental factors in variable combinations contribute to the development of the disease, which presents the main obstacle in search for an effective treatment. In this review, pathogenetic background of type 1 diabetes is discussed, followed by potential immunotherapy approaches for targeting specific immune pathways to prevent or reverse the disease and a short overview of cell therapies. The major focus is on gene therapy. Main concepts and the most commonly used delivery vectors are presented as well as some more detailed description of the preclinical studies that show promising results and might present hope for the future.
Keywords: gene therapy; gensko zdravljenje; immunotherapy; Imunoterapija; Sladkorna bolezen tip 2; sladkorna bolezen tipa 1; type 1 diabetes